P87 Mesenchymal splice isoform fibroblast growth factor receptor (FGFR2c) is an independent prognostic biomarker and further refines risk stratification within endometrial cancer molecular subtypes. (1st November 2019) - Sengal, A; Williams, E; McAlpine, J; Pollock, P
Abstract : Introduction/Background: Four pragmatic molecular subtypes of endometrial cancer (EC) has been established and these seem promising approach in risk stratification. The mismatch repair deficient (MMRd) and p53 wildtype subtypes are the most common and given their molecular subgroups with intermediate prognosis additional biomarkers to further stratify these groups are needed. Fibroblast growth factor receptor (FGFR2) has two major splice isoforms, FGFR2b and FGFR2c. FGFR2c is an oncogen and has been associated with aggressive tumour behaviour in several cancers. The objective was to investigate the role of FGFR2c in progression and risk stratification within the MMRd and p53 wt subtypes. Methodology: We have developed, optimized and validated a novel RNA in situ hybridization assay to detect FGFR2c. Expression was determined in screening cohort of ECs (n=78) and the clinically annotated Canadian cohort (n=465). Kaplan Meier curve and Cox regression model analyses were performed to assess the prognostic value of FGFR2c. Results: There was a significant difference in mRNA FGFR2c expression between endometrioid EC and non-endometrioid EC, 50% versus 23%, p<0.0001. Univariable analysis revealed FGFR2c was significantly associated with shorter Disease Specific Survival (p<0.001) and Progression-free Survival (p<0.009) in endometrioid EC. Multivariable Cox regression analysis showed patients with FGFR2c expression have reduced DSS (p<0.022) and PFS (p<0.035). Specifically, within the MMRd molecular subtype FGFR2c expression was significantly associated with shorter DSS (p<0.001) and PFS (p<0.048) and this trend was also evident in the p53 wildtype subtypes. Conclusion: FGFR2c is an independent prognostic biomarker in EC and its expression further discerns the outcome of EC patients with molecularly classified MMRd and p53 wildtype tumours. Integration of FGFR2c into the new molecular subtyping can further refine risk stratification of endometrioid EC. Disclosure: Nothing to disclose.